«The cavalry rushes, and in battle campaigns the tank rushes along with the war horse»: cavalry romance in Soviet songs on eve of the Great Patriotic War - A. V. Rychkov (Омский научный вестник: Серия "Общество. История. Современность")
The publication analyzes the content component of the phenomenon of Soviet pre-war «cavalry» songs. Particular attention is paid to the role of public cultural policy, with the help of art forming a system of values among Soviet people, where the patriotic idea of defending the homeland was the most important element. The author explains the popularity of the subject both as traditional for that time about the significant role of cavalry in the Red Army, its high combat qualities and the prospect of using it in combination with other types of troops, and the government’s campaign «for the Soviet Cossacks», in which the cavalry song was the most important propaganda tool. According to the author, the songs about cavalry written by talented poets and composers were loved by the people and became the most important means of military-patriotic education of Soviet people, making a significant contribution to the Great Victory